INCOME DISTRIBUTION AND THE FACTORS THAT INFLUENCE OF INCOME OF RUBBER FARlffiR IN SIGUNTUR VILLAGE, SITIUNG SUBDISTRICT DHARMASRAYA REGENCY - Eflita, Rita - (Pendidikan Ekonomi, 2014)
This research is to analyse of income distribution and the factors that influence of income of rubber farmer in Siguntur Village, Sitiung Subdistrict Dharmasraya Regency. This Research is descriptive associative. The data of research are primary and secondary. Amount of population are 925 chairman of family and amount of sample which is taken is 90 chairman of family. A slovin formula till alternative take purposive sampling. Data analyse is descriptive, Gini Ratio analyse of inductive which consist of model reasonable test, classic assumption test, re!,>ressions analyse, coefficient of determinasi, and hypothesis test. Gini Ratio see high and low disrtibusi of people earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency. The result of this research show condition of distribution decreasing of farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency the result of gini ratio 0,59 that mean distribution of the farmer earning is located in strong decreasing category. The result of analysis Regression show that (1) Wide of farm have a significant to farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency where is value thitung is 36,64 > ttabel is 1,99 and the value sig is 0,000 < 0,05 it means HI is received HO is refused. (2) a seed has a significant to farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency where is the value thitung is 3,96 > ttabel is 1,99 and the value sig is 0,000 < 0,05 it means H2 is received HO is refused. (3) the kindness ofEnergy has a significant to farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency where is thitung is 3,76 > ttabe/1,99 and value sig 0,000 < 0,05 it means H3 received HO is refused. (4) the price has a significant to farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya Regency where is the value thitung is to 3,13 > ttabel is 1,99 and the value sig 0,002< 0,05 it means H4 is received HO is refused (5) Wide Off arm, a seed, Kindness Energy and Price have significant totally about farmer earning in Siguntur Village Sitiung Subdistrict DharmasrayaRegency where is the value Fhitung is 423,214 > Ftabel is 2,47 and the value sig is 0,000 < 0,05, it means H5 is received HO is refused.